2019
DOI: 10.1002/jsp2.1050
|View full text |Cite
|
Sign up to set email alerts
|

Annulus fibrosus cell sheets limit disc degeneration in a rat annulus fibrosus injury model

Abstract: In recent years, studies have explored novel approaches for cell transplantation to enable annulus fibrosus (AF) regeneration of the intervertebral disc in particular for lumbar disc herniation. Nevertheless, successful engraftment of cells is structurally challenging, and no definitive method has yet been established. This study investigated the potential of cell sheet technology to facilitate cell engraftment for AF repair. AF injury was induced by a 1 × 1 mm defect in rat tails after which AF cell sheets we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 60 publications
(130 reference statements)
1
12
0
Order By: Relevance
“…Many studies have recorded disc height loss after AF injury, and disc height is considered a benchmark for both degeneration and success of the repair strategy clinically 55 . The results in this study are in agreement with multiple studies that have shown successful repair of the injuries to the central AF in vivo 18,23,27‐29 . Both in terms of significant height loss in injured IVDs and disc height restoration and improvement due to repair.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Many studies have recorded disc height loss after AF injury, and disc height is considered a benchmark for both degeneration and success of the repair strategy clinically 55 . The results in this study are in agreement with multiple studies that have shown successful repair of the injuries to the central AF in vivo 18,23,27‐29 . Both in terms of significant height loss in injured IVDs and disc height restoration and improvement due to repair.…”
Section: Discussionsupporting
confidence: 88%
“…55 The results in this study are in agreement with multiple studies that have shown successful repair of the injuries to the central AF in vivo. 18,23,[27][28][29] Both in terms of significant height loss in injured IVDs and disc height restoration and improvement due to repair. These studies were done on small animal models, where the size of the defect is smaller and biomechanical requirements on the repair construct are much lower than in large animals.…”
Section: Mechanical and Biological Evaluation Of The Endplate Delammentioning
confidence: 99%
See 2 more Smart Citations
“…Besides the physical support, bioadhesives have been evolved to deliver bioactive cues and/or cells in addition to provide tissue adhesion [13,14,[17][18][19]. Bioadhesives applied on injured site can serve as effective localized delivery vehicles as secured in situ [13,14,[17][18][19] or providing physical and/or biochemical environment promoting tissue repair [20,21]. Recent improvements in the design and synthesis of bioadhesives have made steps closer to successful applications for musculoskeletal tissues in high mechanical demand.…”
Section: Introductionmentioning
confidence: 99%